Secondary Metabolites of Hypericum leptophyllum Hochst., an Endemic Turkish Species. (29th April 2012) - Camas, Necdet; Radusiene, Jolita; Stanius, Zydrunas; Caliskan, Omer; Cirak, Cuneyt
Abstract : In the present study, the presence of the phloroglucinol derivative hyperforin, the naphthodianthrones hypericin and pseudohypericin, the phenylpropane chlorogenic acid and the flavonoids rutin, hyperoside, kaempferol, isoquercetine, quercitrine, and quercetine was investigated in Hypericum leptophyllum Hochst., an endemic Turkish species for the first time. The aerial parts representing a total of 30 individuals were collected at full flowering and dissected into floral, leaf, and stem tissues. After being dried at room temperature, the plant materials were assayed for secondary metabolite concentrations by HPLC. Aerial plant parts accumulated chlorogenic acid, hyperoside, isoquercetine, quercitrine, and quercetine, but they did not accumulate hyperforin, hypericin, pseudohypericin, rutin, and kaempferol. Accumulation levels of the detected compounds varied with plant tissues. Such kind of data could be useful for elucidation of the chemotaxonomical significance of the corresponding compounds and phytochemical evaluation of this endemic species.